First insight into H3K4me3 modification in the rapid growth of Alexandrium pacificum (dinoflagellates) - Qi, Juan; Zhu, Zhimei; Liu, Yuan; Sui, Zhenghong (Frontiers in Marine Science, 2022)
Alexandrium pacificum is a dinoflagellate species notorious for its rapid growth resulting in large-scale blooms. This study aimed to investigate the molecular mechanisms of A. pacificum under laboratory-simulated rapid growth conditions from the perspective of H3K4me3 modification regulation. Western blot was used to detect the modification abundance of H3K4me3 in A. pacificum cultured under different conditions, including high light (HL), high nitrogen (HN), and f/2 medium (control, CT), in the rapid growth exponential phase. The results showed that the modification abundance of H3K4me3 under HL or HN was greater than that under CT. Chromatin immunoprecipitation-sequencing was used to explore the acting genes of H3K4me3 under different conditions for the first time. Nitrogen metabolism and endocytosis were significantly associated with H3K4me3 regulation under HL.Furthermore, H3K4me3 was also significantly associated with the vitamin metabolism pathway under HN. These findings demonstrate that H3K4me3 plays a potentially important role in the regulation of the rapid growth of A. pacificum. Such knowledge of a histone modification regulatory network in this dinoflagellate, lays a necessary foundation for future research in related fields.